So done - Chase, Paula (Greenwillow Books, 2019)
Jamila and Metai have been best friends for years, but something happened at the end of seventh grade that they won't speak about, and it tore their friendship apart. Taking a break from each other proves hard given that they live across the street from one another and are both auditioning for the gifted and talented dance program at their school.